2017
DOI: 10.1371/journal.pone.0169252
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study on Applying Radiophotoluminescent Glass Dosimeters for CyberKnife SRS Dose Verification

Abstract: CyberKnife is one of multiple modalities for stereotactic radiosurgery (SRS). Due to the nature of CyberKnife and the characteristics of SRS, dose evaluation of the CyberKnife procedure is critical. A radiophotoluminescent glass dosimeter was used to verify the dose accuracy for the CyberKnife procedure and validate a viable dose verification system for CyberKnife treatment. A radiophotoluminescent glass dosimeter, thermoluminescent dosimeter, and Kodak EDR2 film were used to measure the lateral dose profile a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…As per our expectations, notable dose differences should have been obtained because this study employed PLA filament. However, the dose difference between the anthropomorphic head phantom and the 3D-printed phantom was almost within the measurement uncertainty for the RPL glass dosimeter [23,30]. A factor contributing to this result may be the low CT value in the infill region of the 3D-printed phantom, as discussed in the previous section.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…As per our expectations, notable dose differences should have been obtained because this study employed PLA filament. However, the dose difference between the anthropomorphic head phantom and the 3D-printed phantom was almost within the measurement uncertainty for the RPL glass dosimeter [23,30]. A factor contributing to this result may be the low CT value in the infill region of the 3D-printed phantom, as discussed in the previous section.…”
Section: Discussionmentioning
confidence: 60%
“…In Japan, postal dose audits have been performed on radiation therapy units using RPL glass dosimeters since 2007 [29] and previous studies have employed RPL glass dosimeters for radiotherapy dose verification. Hus et al compared measurements from an RPL glass dosimeter with those from a thermoluminescent dosimeter and radiographic film, and found differences less than 5%, which is clinically acceptable accuracy [30]. Nakaguchi et al also reported that the accuracy of the RPL glass dosimeter measurement was almost 5% and that angular dependency and geometric uncertainties should be considered [23].…”
Section: Discussionmentioning
confidence: 99%